User Acceptance Of Ipm Approaches: A Case Of Vegetable Farmers In Albert Luthuli,South Africa (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The integrated pest management is a robust model in response to the effects of the use of pesticides. The intention to adopt the integrated pest management approaches as farm management practice amongst vegetable farmers was the primary objective of this study. The study used principal component analyses to simplify the statements elicited from 600 farmers using the theory of planned behaviour which includes attitude, subjective norms and perceived behavioural control. The study applied the modified theory of planned behaviour approach to illustrate factors influencing farmers’ extant intentions to adopt integrated pest management. The ordinal regression model-polytomous universal model was used for analysis. The findings indicated that there are heterogeneity of factors influencing the intention to use integrated pest management in farming practice. However, government policy response does not constitute an important driver of intention to use integrated pest management.  The study concluded that the intention to adopt integrated pest management practices is governed by both psychological and social milieus. Furthermore, the potentials of farmers and diversity of available resources must be accentuated in agricultural policy planning to raise the intention to adopt integrated pest management.